(untitled) (مجلة إحالات, 2026)
This study explores the presence of the "narrator" in its various forms in the collection "Shattered Pitchers" by the Iraqi poet Abdul Wahhab Al-Bayati, revealing the aesthetics of the narrative details employed by the poet in this collection. The research begins with the climax hypothesis that AlBayati The research explores the manifestations of the narrator: tracing the ideas that focus on the narrator’s voice in the collection’s poems, whether as an omniscient narrator, a participant in the events, or hidden behind the pronouns of the speaker, the addressee, or the narrator. In addition to the distance separating the narrator from the events and characters, this is found in the types of narration and the perspective. and other effects that lend the poetic text a pictorial character and also contribute to shaping its aesthetics. We will explore the multiplicity of narrators among the authors and among the various poems in the collection, and how this diversity contributes to influencing the horizons of interpretation. We will explore the artistic and aesthetic implications of this diversity of narrative voices, and how Al-Bayati was able to skillfully employ the techniques of correspondence in a unique and distinct poetic experience in his collection "Shattered Pitchers," which subsequently helped us understand this pioneering poetic work.